Holm oak proteomic response to water limitation at seedling establishment stage reveals specific changes in different plant parts as well as interaction between roots and cotyledons - Simova Stoilova, Lyudmila P. (2018)
Quercus ilex is a dominant tree species in the Mediterranean region with double economic and ecological importance and increasing use in reforestation. Seedling establishment is extremely vulnerable to environmental stresses, particularly drought. A time course study on physiological and proteomic response of holm oak to water limitation stress and recovery during early heterotrophic growth is reported. Applied stress led to diminution in plant water content and root growth, oxidative stress in roots and some alterations in the anti-oxidative protection. Plant parts differed substantially in soluble sugar and free phenolic content, and in their changes during stress and recovery. Proteomic response in holm oak roots and cotyledons was estimated using combined 1-DE/2-DE approach and protein identification by MALDI TOF-TOF PMF and MS/MS. A total of 127 differentially abundant protein species (DAPs) were identified. DAPs related to starch metabolism, lipid to sugar conversion, reserve proteins and their mobilization were typical for cotyledons. DAPs in roots were involved in sugar utilization, secondary metabolism and defense, including pathogenesis related proteins from PR-5 and PR-10 families. Results emphasize specific proteome signatures of separate plant parts as well as importance of sink-source interaction between root and cotyledon in the time course of stress and in recovery.